Determination of linear alkylbenzene sulfonates in water samples by liquid chromatography-UV detection and confirmation by liquid chromatography-mass spectrometry - Wangkarn S. (2014)
A high-performance liquid chromatographic (HPLC) method was developed for the separation and determination of individual (C10-C13) linear alkylbenzene sulfonates (LAS). New sets of conditions have been established for routine analysis of individual chemical forms of four LAS surfactants, i.e. C10-C13 LAS. Under a condition set using a mobile phase containing 1.5 mM ammonium acetate in methanol/water 80:20 (v/v) mixture, detection limits obtained were in the range 1.5 ppb (for C 10 LAS) to 11.5 ppb (for C13 LAS). This offers the advantages of significant improvement in resolution, short separation time and using less amount of common salt under isocratic condition. In addition, the use of simple mobile phase containing a simple low amount of salt cannot deposit at the entrance of mass spectrometric detector. The method is applicable to the simultaneous determination of LAS surfactants in various water samples. LAS surfactants presented in these samples were also successfully confirmed by using electrospray mass spectrometry. © 2005 Elsevier B.V. All rights reserved.